"Hard to Say Goodbye Over iPad": Experiences of Palliative Care Providers and Lessons Learned During the COVID-19 Pandemic in Rural Communities of Indiana, United States. Issue 3 (14th June 2022) - Lalani, Nasreen; Cai, Yun; Wang, Yitong
Abstract : The need for palliative care (PC) has gained increased attention during the COVID-19 pandemic. Palliative care adds an extra layer of support and care for patients with advanced chronic illnesses and their families. Because of pandemic restrictions, access and provision of PC services were challenging and resulted in huge suffering and caregiving burden among patients with advanced chronic illnesses and their families, especially those living in smaller towns and rural communities. The study aimed to describe the impact of COVID-19 on PC services and examine various ethical, moral, and practice issues and challenges experienced by rural providers. Using a community-based participatory research approach, a purposive sample of health care providers (n = 15) was obtained from smaller towns and rural communities in Indiana, United States. Online individual interviews were used for data collection. Thematic analysis showed several concerns including restricted visitation, communication challenges, "hard to say goodbye over iPad", moral distress among providers, and preference for home hospice services. Findings call for strategies to implement best PC practices and programs to support providers and families in smaller towns and rural communities.